Effect of equal channel angular pressing process on drawability of DC04 steel sheets - Talantikite M.; Mebarek A.; Zaaf M.; Boukeffa S. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Equal channel angular pressing (ECAP) is a severe plastic deformation (SPD) technique that induces substantial changes in the crystalline structure of materials, leading to enhanced mechanical properties. The aim of this experimental work is to study the influence of ECAP on the drawability of DC04 steel sheets. A multilayer sample of six sheets was deformed at room temperature with an internal channel angle of 120° in a single pass. The characterization was performed by measuring hardness and performing tensile tests, along with optical microscopy and X-ray diffraction (XRD) analysis. In addition, a finite element simulation was carried out with Abaqus. The Erichsen test was used to assess the drawability of the sheet with the best mechanical properties. The results showed a significant increase in microhardness, with an improvement of 64% compared to the original microhardness. Microstructural analysis showed a 70% reduction in grain size, with slight texture formation and no phase change. Tensile tests showed an increase in yield stress (Re) and ultimate tensile strength (Rm), accompanied by a decrease in elongation (A%) and strain hardening exponent (n). The Erichsen test demonstrated a slight 10% reduction in the Erichsen cupping index (IE). Overall, we succeeded in improving the mechanical properties of the DC04 steel plates while maintaining good drawability.